1987
DOI: 10.1146/annurev.nu.07.070187.001033
|View full text |Cite
|
Sign up to set email alerts
|

Diseases Associated with Defects in Vitamin B6 Metabolism or Utilization

Abstract: It is clear that many diseases are known to involve defects in vitamin B6 metabolism, but that even more await definitive studies. Furthermore, some functions of vitamin B6, such as its role in glucocorticoid action (21), have been discovered so recently that the medical implications have not yet been fully explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 90 publications
1
38
0
1
Order By: Relevance
“…A possible explanation could be that plasma PLP is bound to serum albumin while being transported by the blood; however, low serum albumin in our critically ill patients caused the dephosphorylation of plasma PLP into PL (Merrill and Henderson, 1987).…”
Section: Discussionmentioning
confidence: 85%
“…A possible explanation could be that plasma PLP is bound to serum albumin while being transported by the blood; however, low serum albumin in our critically ill patients caused the dephosphorylation of plasma PLP into PL (Merrill and Henderson, 1987).…”
Section: Discussionmentioning
confidence: 85%
“…Erythrocyte PLP status should be considered when assessing vitamin B6 status in the critically ill. Pyridoxal 5'-phosphate and PL are both bound to serum albumin, with the PLP binding more tightly, against rapid hydrolysis by alkaline phosphatase while being transported by the blood. Lower serum albumin levels in our critically ill patients may lead to the dephosphorylation of plasma PLP into PL (Merrill & Henderson, 1987). Because dietary vitamin B6 and protein intake as well as plasma alkaline phosphatase activity may affect plasma PLP concentration, recent research has suggested that plasma PL may be useful as an indicator for vitamin B6 status (Leklem, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…PN therapy is frequently recommended for various conditions, including genetic disorders, such as cystathioninuria and homocystinuria, and a range of other disorders, such as premenstrual tension, seizures, carpal tunnel syndrome, and the nausea and vomiting that can occur during pregnancy (1,3,(21)(22)(23). Because it is considered a safe compound, very high doses of B 6 [Ͼ2000-fold higher than the recommended dietary allowance (1.4 -2.1 mg/day, depending on sex and age)] are used in some circumstances (7,24 ).…”
mentioning
confidence: 99%